2017
DOI: 10.1093/biolre/iox129
|View full text |Cite
|
Sign up to set email alerts
|

Generation of transgenic marmosets using a tetracyclin-inducible transgene expression system as a neurodegenerative disease model†

Abstract: Controllable transgene expression systems are indispensable tools for the production of animal models of disease to investigate protein functions at defined periods. However, in nonhuman primates that share genetic, physiological, and morphological similarities with humans, genetic modification techniques have not been well established; therefore, the establishment of novel transgenic models with controllable transgene expression systems will be valuable tools to understand pathological mechanism of human dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…It appears that although ubiquitously expressed promoters induce strong transgene expression, they also lead to clinically irrelevant symptoms. Therefore, in addition to previous SCA3 model marmosets whose transgenes were driven by the CMV promoter, we generated a transgenic marmoset model line of SCA3 in which transgenes were controlled by the Tet-inducible gene expression system (Tomioka et al, 2017b). The ability to control the disease onset is an important advantage in biomarker development studies because it allows us to define the disease onset at the molecular level.…”
Section: Transgenic Marmoset Model Of Sca3 With Tetracycline (Tet)-inmentioning
confidence: 99%
“…It appears that although ubiquitously expressed promoters induce strong transgene expression, they also lead to clinically irrelevant symptoms. Therefore, in addition to previous SCA3 model marmosets whose transgenes were driven by the CMV promoter, we generated a transgenic marmoset model line of SCA3 in which transgenes were controlled by the Tet-inducible gene expression system (Tomioka et al, 2017b). The ability to control the disease onset is an important advantage in biomarker development studies because it allows us to define the disease onset at the molecular level.…”
Section: Transgenic Marmoset Model Of Sca3 With Tetracycline (Tet)-inmentioning
confidence: 99%
“…Regarding aging research, many of the transgenic lines proposed and developed using marmosets have focused on neurologic disease and modeling of neurodegenerative disorders such as Alzheimer's and Parkinson's. Lentiviral transgenic induction of Tet-on human ataxin 3 genes has produced young marmosets with neurodegenerative disease phenotype [81,82]. Recently, marmosets that express transgenic induction of intracellular calcium indicators have been developed in order to greatly advance the technology and imaging possibilities [83].…”
Section: Scientific Approaches To Study Aging In Marmosetsmentioning
confidence: 99%
“…Two offspring exhibited whole‐body expression of the EGFP reporter . Then, lentivirus was used to create transgenic marmoset and cynomolgus monkey models …”
Section: The Different Types Of Nhp Transgenic Modelsmentioning
confidence: 99%
“…The mutant human ataxin 3 gene controlled by the tet‐on system was injected into marmoset's embryos via lentiviral transduction. Four of the seven live offspring were transgenic and carried the transgene controlled by the tet‐on system . With the objective to monitor in vivo neural activity, Park et al reported the generation of a transgenic marmoset expressing GCaMP, a genetically encoded calcium indicator, under ubiquitous and neuronal promoters .…”
Section: The Different Types Of Nhp Transgenic Modelsmentioning
confidence: 99%